AUDITORÍA DE GESTIÓN A LA UNIDAD EDUCATIVA COMUNITARIA INTERCULTURAL BILINGÜE “ABC” DE LA PARROQUIA DE TENTA DEL CANTÓN SARAGURO, PROVINCIA DE LOJA. PERIODO 01 DE ENERO AL 31 DE DICIEMBRE DEL 2014” - Tene Obando, Lizbeth Esperanza (2016)
The present thesis work is titled AUDITORÍA DE GESTIÓN A LA UNIDAD EDUCATIVA COMUNITARIA INTERCULTURAL BILINGÜE “ABC” DE LA PARROQUIA DE TENTA DEL CANTÓN SARAGURO, PROVINCIA DE LOJA. PERIODO 01 DE ENERO AL 31 DE DICIEMBRE DEL 2014, the outlined objectives are directed to evaluate the system of internal control to verify if the controls implemented by the entity guarantee an efficient development of the academic-administrative activities, to verify that the entity audited fulfills norms and legal other dispositions that are him/her applicable, to apply indicators of efficiency and effectiveness to determine if the objectives and goals were achieved foreseen by the Institution and to present a report that contains comments, conclusions and recommendations that you/they help to the opportune one taking of decisions on the part of the directive of the Institution. The methodology used for the execution of the audit and to fulfill the objectives, was first performed preliminary knowledge of the company, then develop the memorandum of planning and preparing the audit program in which the procedures are determined use; followed by this implementation phase was conducted using internal control questionnaires which allowed the evaluation of it and the selection of objects, knowing the weaknesses, for which narrative bonds were made in stating the rules or broken laws will ; indicators of efficiency and effectiveness were applied to 5 establish the degree of compliance with institutional activities and finally on the basis of the results obtained to issue a report including the respective comments, conclusions and recommendations. In the results it was determined that the institution to appoint the Rector and Inspector is not done through competitive merit and opposition as established by the Organic Law of Intercultural Education (LOEI), there is no control of the Kichwa language by staff administrative and teaching and have not been established performance indicators to measure in terms of efficiency and effectiveness of compliance activities, has been neglected aspect of the training of teachers, not evaluated in-house staff but only It has done externally by the Ministry of Education and there are some teachers who perform functions that are not commensurate with their professional profile. Finally a report is submitted to the Rector with the respective conclusions and recommendations to assist timely decision making.